A Theorisation on the Impact of Responsive Corporate Social Responsibility on the Moral Disposition, Change and Reputation of Business Organisations - Tan, Seng Teck; Liau, Chee How; Nanthakumar, Karuppiah (Canadian Center of Science and Education, 2018)
Corporate social responsibility has been a densely researched area. Research paradigms have evolved significantly stamping from a sociological focus to a more business integrated framework and the currently growing emphasis on quantifying its performance. However, while much literatures champion the proponents of a proactive corporate social responsibility, the contributions of the more responsive version have been largely under studied. This is not an empirical paper. Far from it, this paper attempts to unveil the current literature gaps pertaining to responsive corporate social responsibility. This paper explores the intrinsic contributions of responsive corporate social responsibility on the moral discourse, organisational change and reputation management in an organisation. It theorises the concept of responsive corporate social responsibility as a moderator of external pressures, as a vector of a moral reboot in organisation change and a device for salvaging reputational damage in business organisations. This paper draws from the literature gaps between studies of normative morality and its interaction in principles of general management, organisational change concepts, branding and corporate reputation. It underwrites to examine the moral contents and discourse of business firms when faced with hostile externalities and studies the moral entrails in its organisational change processes and sequentially how this implicates the corporate reputation of a firm. This paper argues that the impacts of responsive corporate social responsibility and its ability to impact moral dispositions in business organisations deserve closer scrutiny. Study on the influence of responsive corporate social responsibility on organisation change and reputational salvage has similarly is also underscored. This article provides a theoretical review of the emerging gaps in corporate social responsibility and prompts that the concept of responsive social responsibility warrants closer attention